Mathematical model of thermal destruction of polymer composition materials - Клюс, В. В.; Кузяев, А. В. (Proceedings of National Aviation University (archive), 1999)
Considered is the process of heat propagation in armored plastic both under moderate temperatures and binder thermal destruction. Worked out is the method of determining kinematic parameters of the thermal destruction process and thermophysical characteristics of materials when chemical reaction is going on in then. As the result a mathematical model was built which allows to carry out tests of polymer composition materials with the help of computer and to exercise optimal collection of components which would meet the desired conditions